Structures and Architecture : REstructure REmaterialize REthink REuse - Mario Rinke; Marie Frier Hvejsel (CRC Press, 2025)
Structures and Architecture - REstructure REmaterialize REthink REuse contains the contributions to the 6th International Conference on Structures and Architecture (ICSA 2025, Antwerp, Belgium, 8-11 July 2025). As a response to the pressing global climate and energy crisis, and with new settings and tools, the design and construction of our built environment needs reconsideration and extension. The papers call for a re-imagination of current practices regarding structures and architecture.The volumes of the series are published every three years, in tandem with the conferences organised by the International Association of Structures and Architecture. They aim to reach a global audience of researchers, practitioners, and students, including architects, structural and construction engineers, builders and building consultants, constructors, material suppliers, planners, urban designers, anthropologists, economists, sociologists, artists, product manufacturers, and other professionals involved in the design and realisation of architectural, structural, and infrastructural projects.